Functional haplotypes of PADI4: relevance for rheumatoid arthritis specific synovial intracellular citrullinated proteins and anticitrullinated protein antibodies. Issue 9 (10th March 2005) - Cantaert, T; Coucke, P; De Rycke, L; Veys, E M; De Keyser, F; Baeten, D
Abstract : Background: Haplotypes of PADI4, encoding for a citrullinating enzyme, were associated with rheumatoid arthritis in a Japanese population. It was suggested they were related to the presence of anticitrullinated protein antibodies (ACPA). Objective: To explore the relation between PADI4 haplotypes, the presence of rheumatoid arthritis specific intracellular citrullinated proteins in synovial membrane, and serum ACPA titres. Methods: Synovial biopsies and peripheral blood samples were obtained in 59 patients with rheumatoid arthritis. Synovial intracellular citrullinated proteins were detected by immunohistochemistry. Serum ACPA titres were measured by anti-CCP2 ELISA. PADI4 haplotypes were determined by direct sequencing of the four exonic PADI4 single nucleotide polymorphisms. Results: PADI4 haplotype frequencies and the presence of synovial intracellular citrullinated proteins and ACPA were comparable with previous studies. There was no significant association between PADI4 haplotype 1 or 2 and the presence of synovial intracellular citrullinated proteins, although these proteins were associated with higher serum ACPA. There was no correlation between PADI4 haplotypes and serum ACPA, either by continuous analysis using the titres or by dichotomous analysis using the diagnostic cut off. Further analyses in homozygotes for haplotype 1 or 2 or in heterozygotes (1/2) also failed to show an association between PADI4 polymorphisms and ACPA. This contrasted with the clear association between ACPA levels and HLA-DR shared epitope. Conclusions: The link between synovial intracellular citrullinated proteins and ACPA emphasises the role of deimination of synovial proteins in rheumatoid arthritis, but the biological relevance of the PADI4 haplotypes for this autoimmune process is questionable, at least in a European population.